“THE STRUCTURE AND FUNCTION OF DIALECTS IN UZBEK AND TURKMEN LANGUAGES” - Charyyeva Dilnoza Allakulovna (Web of Journals Publishing, 2025)
This article explores the structural features and functional roles of dialects within the Uzbek and Turkmen languages. Through comparative linguistic analysis, it identifies similarities and distinctions in phonology, morphology, syntax, and lexical variation. It also highlights the sociolinguistic relevance of dialects in shaping regional identity, preserving linguistic diversity, and facilitating communication in multilingual environments. Drawing on scholarly research and field studies, the paper argues that dialects serve not only as linguistic phenomena but also as cultural repositories that reflect historical and ethnic complexities.
Keywords: Uzbek, Turkmen, dialectology, phonology, morphology, regional variation, sociolinguistics, Turkic languages.